Emergency Department‐Attended Injuries Resulting from School‐Based Violence in Baltimore Adolescents, 2019‐2020. (25th November 2022) - Walter, Creason; Miller, Mattea; Jones, Vanya; Ryan, Leticia Manning
ABSTRACT: BACKGROUND: Our objective is to describe violence‐related injuries to early adolescents that occurred at school, resulting in emergency department (ED) evaluation. METHODS: This retrospective cohort study at an urban academic pediatric ED in Baltimore, MD, identified patients 10‐15 years old who presented with an injury from intentional, interpersonal violence that occurred at school between January 2019‐December 2020. Descriptive statistics were used to summarize patient and event characteristics. RESULTS: Of 819 youth 10‐15 years of age evaluated for a violence‐related injury, school was the location in 115 cases (14.0%). All events occurred prior to the statewide stay at home order (March 30, 2020). School‐injured youth had a mean age of 12.7 ± 1.7 years and were predominantly male (64.3%). Of the 115 cases, 75 (65.2%) involved an altercation with a peer, 26 (22.6%) involved a teacher or school staff, 6 (5.2%) involved a family member, 1 (0.9%) involved police, 6 (5.2%) involved an unknown party, and 1 (0.9%) involved an unrelated but known adult. All injured youth were discharged from the ED. CONCLUSIONS: School‐based violence is a well‐recognized cause of traumatic injuries to adolescents and may involve peers, teachers, or school staff.